Military power and popular protest : the U.S. Navy in Vieques, Puerto Rico - McCaffrey, Katherine T., 1966- (Rutgers University Press, 2002)
Residents of Vieques, a small island just off the east coast of puerto Rico, live wedged between an ammunition depot and live bombing range for the U.S. Navy. Since the 1940s when the navy expropriated over two-thirds of the island, residents have struggled to make a life amid the thundering of bombs and rumbling of weaponry fire. Like the army's base in Okinawa, Japan, the facility has drawn vociferous protests from residents who challenged U.S. security interests overseas. In 1999, when a local civilian employee of the base was killed by a stray bomb, Vieques again erupted in protests that have mobilized tens of thousands of individuals and have transformed this tiny Caribbean Island into the setting for an international cause celebre.